Análise do setor de manutenção de uma universidade pública : hospital universitário - Silva, Dolival Campelo da (2016)
The public university hospitals provide health care services to the population, develop training activities for human resources from different areas and for that alone, it requires a highly complexed organized structure. among all of the departaments, maintenance stands out the most, which seeks to offer actions that ensure the performance of an equipment or system with quality, according to the function for which it was created for and that interferes directly in the public service. The goal of this research is to analyze the maintenance of a public university hospital, describing its characteristics, challenges, and opportunities for improvement. The study was carried out through case studies, many questions and document analysis. Among all aspects raised, we should consider that the administration should not be restricted to only administrative and bureaucratic aspects, must embrace and meet the needs of the human capital of the organization, and include new forms of management, so that the participants are welcomed and continually seek his best performance